Intrapartum Group B Streptococcus Antibiotic Prophylaxis in Penicillin Allergic Pregnant Women - Desravines, Nerlyne; Venkatesh, Kartik K.; Hopkins, Austin; Waldron, Jamie; Grant, Megan; McGuire, Colleen; Boggess, Kim A. (American Journal of Perinatology Reports, 2019)
Objectives To estimate the prevalence of and identify modifiable risk factors for alternative antibiotics for group B Streptococcus (GBS) prophylaxis in penicillin-allergic women.Methods Retrospective cohort study of pregnant women within a health care network from January 1, 2014, to December 31, 2017. Included women were GBS colonized, delivered at ≥ 37 weeks' gestation, and reported penicillin/cephalosporin allergy. The primary outcome was the use of alternate antibiotics GBS prophylaxis, defined per Centers for Disease Control and Prevention guidelines as antibiotics other than penicillin, ampicillin, or cefazolin.Results We identified 190 GBS-colonized pregnant women self-reporting a penicillin/cephalosporin allergy; 5% reported anaphylaxis, 44% high-risk symptoms (isolated hives, shortness of breath, swelling, or vomiting), and 51% low-risk symptoms (isolated rash, itching, or nausea). Two-thirds (63%) had alternative antibiotic prophylaxis. In adjusted analyses, nonwhite race (adjusted odds ratio [aOR]: 2.42; 95% confidence interval [CI]: 1.19–4.94) and high-risk allergic reaction (aOR: 2.42; 95% CI: 1.30–4.49) were associated with higher odds of alternative antibiotics prophylaxis compared with low-risk allergic reaction. Low-risk allergic reaction group was less likely to receive alternative antibiotic prophylaxis (aOR: 0.36; 95 CI%: 0.19–0.66).Conclusion Alternative antibiotic use for GBS prophylaxis is frequent with penicillin/cephalosporin allergies. Efforts to confirm allergy and perform penicillin hypersensitivity testing may increase compliance with guidelines for antibiotic administration.
Keywords: GBS prophylaxis; penicillin allergy; cephalosporin allergy